PENINGKATAN MOTIVASI DAN HASIL BELAJAR MUATAN IPA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MACTH SISWA SD - Puji Anjaswari; Gamaliel Septian Airlanda (Pedagogik : Jurnal Ilmiah Pendidikan dan Pembelajaran Fakultas Tarbiyah Universitas Muhammadiyah Aceh, 2019)
This Classroom Action Research uses the Kemmis and Taggart designs which consist of 2 cycles. Each cycle has a stage of planning, implementation and observation, as well as reflection that aims to improve motivation and learning outcomes in theme 3 of the sub-theme 2 of the IPA content using the learning model make a macth. The subjects of the study were 4th grade students at SD Negeri Noborejo 01 Salatiga with a total of 34 students. The criteria for success are 80% of students and minimum learning motivation in enough categories. The results of the study show that the learning model using a method can increase the percentage of learning motivation. This can be seen from the percentage of pre cycle 1.92 (47.89%) cycle I 2.62 (64.60%) cycle II 3.52 (91.15%). increasing motivation to learn also has an impact on improving learning outcomes, namely Pre-cycle 51.3 first cycle 75.59, Cycle II 86.4. Thus the model of making a study not only increased learning motivation but also the learning outcomes of science content on 4th grade students at SDN Noborejo 01 Salatiga.